2003
DOI: 10.1128/aac.47.4.1436-1438.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Posaconazole against Pseudallescheria boydii : In Vitro and In Vivo Assays

Abstract: Thirty isolates of Pseudallescheria boydii were tested to compare the in vitro activity of posaconazole with those of fluconazole and itraconazole, using NCCLS methods. Posaconazole was evaluated in an immunosuppressed mouse model of disseminated pseudallescheriasis. Posaconazole was more effective than itraconazole and as effective as fluconazole in preventing death and significantly reducing the CFU of P. boydii from tissues.In the last few decades, Pseudallescheria boydii has emerged as an important human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…In an immunocompromised murine model, posaconazole prolonged survival by 70 to 75% at dosages of Ͼ30 mg/kg/day. Surprisingly, in the same model, 40 mg/kg/day of fluconazole resulted in 55% survival and a reduced fungal burden (163). The posaconazole and fluconazole MICs in the latter study were 0.125 to 1 g/ml and 32 to Ͼ64 g/ml, respectively.…”
Section: In Vivo Antifungal Therapymentioning
confidence: 66%
See 2 more Smart Citations
“…In an immunocompromised murine model, posaconazole prolonged survival by 70 to 75% at dosages of Ͼ30 mg/kg/day. Surprisingly, in the same model, 40 mg/kg/day of fluconazole resulted in 55% survival and a reduced fungal burden (163). The posaconazole and fluconazole MICs in the latter study were 0.125 to 1 g/ml and 32 to Ͼ64 g/ml, respectively.…”
Section: In Vivo Antifungal Therapymentioning
confidence: 66%
“…21,2008 INFECTIONS CAUSED BY SCEDOSPORIUM SPP. 163 the graphium type of conidial state and has not been found to produce a teleomorph (237,349,427). Microscopic features.…”
Section: Scedosporium Prolificansmentioning
confidence: 99%
See 1 more Smart Citation
“…This discordance may be related to the animal model used as well as to pharmacodynamic and pharmacokinetic factors related to the two agents in mice. Even though the therapeutic regimen used in this study was chosen on the basis of pharmacokinetic studies of POS in mice (1,16,17,21,30,31), the resilient nature of the isolate that we used resulted in deep infections that progressively damaged the tissues studied.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses potent antifungal activity against a broad spectrum of fungal pathogens (5,9,11,12,21,22,(31)(32)(33)(34)42). A recent report (16) has demonstrated that POS is active in a murine model of infection due to Scedosporium apiospermum, the second medically important species of the genus Scedosporium.…”
mentioning
confidence: 99%